IMPROVING EFL LEARNERS’ SPEAKING PROFICIENCY THROUGH ROLE PLAY AND DIGITAL MEDIA - Indah Muzdalifah; Dafwen Toresa; Fana Wiza; Vivi Indriyani; Asma Alhusna (English Study Program University of Pasir Pengaraian, 2026)
This study aims to develop an innovative English learning method aligned with Outcome-Based Education (OBE) by integrating role-play and YouTube as a strategy to enhance speaking proficiency among MKDU English students. Through active participation in recorded and published role-play activities, students improve contextual communication skills, confidence, creativity, and digital adaptability. Using a descriptive quantitative approach, the research evaluates the effectiveness of this method via pre- and post-tests and closed questionnaires involving Digital Business students at Universitas Lancang Kuning. Assessment focuses on five indicators: role appreciation, content mastery, cultural gestures, pronunciation, and scene graphic design. The results show measurable improvements: average speaking scores increased by 18% from pre- to post-test, with the highest gain in pronunciation (22%) and content mastery (20%). Questionnaire responses indicate that 87% of students felt more confident and collaborative in communicative tasks. These findings demonstrate that YouTube-based role-play not only strengthens linguistic competence but also directly supports OBE outcomes by fostering reflective, creative, and professional communication skills essential for workplace readiness.